2003
DOI: 10.1046/j.1365-313x.2003.01952.x
|View full text |Cite
|
Sign up to set email alerts
|

The universally conserved HCF101 protein is involved in assembly of [4Fe‐4S]‐cluster‐containing complexes in Arabidopsis thaliana chloroplasts

Abstract: SummaryThe seedling-lethal nuclear Arabidopsis hcf101 (high chlorophyll¯uorescence) mutant is impaired in photosynthesis and complemented by the wild-type HCF101 cDNA. Photosystem I (PSI) activity is abolished, and PSI core complexes fail to accumulate in hcf101, whereas levels of other thylakoid membrane proteins are unaffected. Northern and in vivo labelling analyses as well as studies on polysome loading show that PSI transcript levels and translation rates of proteins, which belong to PSI, are normal in hc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
106
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 77 publications
6
106
0
Order By: Relevance
“…The altered chloroplast ultrastructure observed in CpNifSsilenced lines is reminiscent of the ultrastructure reported for an APO1 mutant (22) that affects PSI accumulation, as well as a mutant in Hcf101 and other mutations that affect PSI (23,24). Therefore, the dilated stromal lamellae and absence of grana may be a consequence of a lack of PSI.…”
Section: Discussionmentioning
confidence: 62%
“…The altered chloroplast ultrastructure observed in CpNifSsilenced lines is reminiscent of the ultrastructure reported for an APO1 mutant (22) that affects PSI accumulation, as well as a mutant in Hcf101 and other mutations that affect PSI (23,24). Therefore, the dilated stromal lamellae and absence of grana may be a consequence of a lack of PSI.…”
Section: Discussionmentioning
confidence: 62%
“…In plants, NIF (17)(18)(19), HCF101 (20), and NFU proteins (35) have been shown to be involved in Fe-S assembly and we recently suggested that Arabidopsis most probably also contains a complete plastid-localized SUF system (23). In support of this notion we have demonstrated that the essential ABC/ATPase AtNAP7 can restore growth defects in a SufCdeficient E. coli mutant demonstrating that Arabidopsis harbors an evolutionary conserved SufC protein (23).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the recent observation that Arabidopsis harbors chloroplast-localized Nif proteins AtCpNIFS/AtNFS2, AtCnfU-V, and AtCnfU-IVb (17)(18)(19) and HCF101 (20) demonstrates that plant Fe-S cluster biogenesis occurs in both mitochondria and plastids. In chloroplasts Fe-S clusters are required for cytochrome b 6 /f complex, ferredoxin and photosystem I ensuring electron flow in the thylakoids (21,22); however, to date Fe-S cluster biogenesis in plastid is poorly understood.…”
mentioning
confidence: 99%
“…Members of the ApbC/Nbp35 family are widely distributed, being found in virtually all organisms in the biosphere (17,20,22). Intriguingly, the requirement for two such P-loop NTPases within the same pathway for FeS cluster biogenesis to date has only been demonstrated in animals and fungi (23).…”
mentioning
confidence: 99%